Corona virus vaccine hesitancy among higher education students in Adama City, Oromia, Ethiopia - Abebe, Dawit; Mengistu, Tewodros; Demssie, Enku Afework; Mesfin, Sinetibeb (Frontiers in Public Health, 2024)
Background Vaccination stands as the most efficient approach for managing the continued transmission of infections and preventing the emergence of novel variants. Coronavirus disease 2019 (COVID-19) vaccine hesitancy poses a significant burden in the fight to achieve herd immunity. Methods A cross-sectional study, based on institutional parameters, was conducted among a cohort of 530 higher education students, selected via a simple random sampling method. Study participants were selected using a systematic random sampling technique from February to March 2022. Structured questionnaire data were gathered and subsequently analyzed using SPSS version 21. The strength of the association between various factors and COVID-19 vaccine hesitancy was assessed using the odds ratio along with its 95% confidence interval. Statistical significance was deemed to be present at a p-value of < 0.05. Result The prevalence of coronavirus vaccine hesitancy was 47.5%. The factors that were found to be significantly associated with COVID-19 vaccine hesitancy were residential address (AOR = 2.398, 95% CI: 1.476–3.896); agreeing with leaders and groups that do not support COVID-19 vaccination (AOR = 2.292, 95% CI: 1.418–3.704); coming from a community whose leaders support COVID-19 vaccination for young adults (AOR = 0.598, 95% CI: 0.381–0.940), and believing that COVID-19 vaccines are safe (AOR = 0.343,95% CI: 0.168–0.701). Conclusion Approximately five out of 10 students who participated in this study were hesitant to get vaccinated against coronavirus. Incorporating messages and initiatives into local plans to specifically target the factors identified in this study is imperative for substantially increasing the COVID-19 vaccine uptake among students in higher education institutions.